2021
DOI: 10.1017/jfm.2021.236
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of different scales of turbulent motions to the mean wall-shear stress in open channel flows at low-to-moderate Reynolds numbers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 70 publications
(166 reference statements)
2
14
0
Order By: Relevance
“…A similar approach was taken by Duan et al. (2021) to study the contribution of different-sized structures to mean wall shear stress in open-channel flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach was taken by Duan et al. (2021) to study the contribution of different-sized structures to mean wall shear stress in open-channel flows.…”
Section: Introductionmentioning
confidence: 99%
“…The most famous of these relationships and the one employed by Deck et al (2014) andDe Giovanetti et al (2016) is the so-called FIK relationship developed by Fukagata, Iwamoto & Kasagi (2002). A similar approach was taken by Duan et al (2021) to study the contribution of different-sized structures to mean wall shear stress in open-channel flows.…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant identity was discovered by Renard & Deck (2016) (hereafter referred to as the RD decomposition), for which the skin-friction coefficient is expressed as the sum of integral terms belonging to the mechanical energy equation. Alternative identities for the skin-friction coefficients of these flows, derived from the vorticity equation, was obtained by Yoon et al (2016), and variants for open-channel flows were studied by Nikora et al (2019) and Duan et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed reviews about methods to measure and estimate shear stress can be found in Huai et al [5]. Experimental setups range from large-scale measurements (e.g., Errico et al [6]) to highly controlled laboratory-based experiments (e.g., Duan et al [7] and Bashirzadeh et al [8]). The direct measurement of shear stress requires sensitivity to small changes in flow velocity, generates minimal flow disturbance, especially in the vicinity of the bed, and maintains the principle of no sliding of the material in the bed [9][10][11].…”
Section: Introductionmentioning
confidence: 99%